Lobular capillary hemangioma in a patient with ankylosing spondylitis using adalimumab: an exuberant presentation, - Thadeu Santos Silva; Carlos Leonardo Martins Guimarães; Isabela Pimenta Xavier; Vitória Regina Pedreira de Almeida Rego (Sociedade Brasileira de Dermatologia, 2020)
Abstract Lobular capillary hemangioma or pyogenic granuloma is a benign vascular tumor of the skin or mucous membranes. Most patients present a single lesion. It manifests clinically as an erythematous, friable, and fast-growing tumor. This report details a case with exuberant presentation in a patient with ankylosing spondylitis, using adalimumab. Factors triggering pyogenic granuloma are not well known. They may spontaneously regress, but most require treatment.